Intramolecular Benzyne–Phenolate [4+2] Cycloadditions. (8th May 2020) - Takikawa, Hiroshi; Nishii, Arata; Takiguchi, Hiromu; Yagishita, Hirotoshi; Tanaka, Masato; Hirano, Keiichi; Uchiyama, Masanobu; Ohmori, Ken; Suzuki, Keisuke
Abstract: An intramolecular benzyne–phenolate [4+2] cycloaddition is reported. Benzyne precursors, having vicinal halogen‐sulfonate functionalities, linked with a phenol(ate) by various tether groups undergo efficient intramolecular [4+2] cycloaddition by treatment with either Ph3 MgLi or n BuLi for halogen–metal exchange to form various benzobarrelenes. Abstract : An intramolecular benzyne–phenolate [4+2] cycloaddition has been developed. Benzyne precursors, having vicinal halogen‐sulfonate functionalities, linked with a phenol(ate) by various tether groups undergo efficient intramolecular [4+2] cycloaddition by treatment with either Ph3 MgLi or n BuLi, for halogen–metal exchange, to form various benzobarrelenes. The method is amenable to various reaction precursors and the products are isolated in high yield.